Influence of stepwise chondrogenesis-mimicking 3D extracellular matrix on chondrogenic differentiation of mesenchymal stem cells. (June 2015) - Cai, Rong; Nakamoto, Tomoko; Kawazoe, Naoki; Chen, Guoping
Abstract: Extracellular matrix (ECM) has drawn a broad attention for preparation of tissue engineering scaffolds and stem cell study. ECM scaffolds stepwise mimicking development of tissues can provide useful models to investigate the interactions between stem cells and ECM during the process of tissue development. In this study, 3D stepwise chondrogenesis-mimicking ECM scaffolds were prepared from mesenchymal stem cells (MSCs) by controlling the stages of chondrogenic differentiation. ECM scaffolds mimicking the early stage and late stage of chondrogenesis were obtained when MSCs were cultured in the chondrogenic medium for 1 and 3 w, respectively. The ECM scaffolds had different compositions as shown by immunohistochemical analysis. Stem cell (SC)-ECM scaffold was rich in collagen I and biglycan. Early stage chondrogenesis-mimicking (CE)-ECM scaffold had moderate amount of collagen II and aggrecan while late stage chondrogenesis-mimicking (CL)-ECM scaffold were rich in collagen II and aggrecan. These three ECM scaffolds had different effects on chondrogenesis of MSCs. The CE-ECM scaffold facilitated chondrogenesis, however the CL-ECM scaffolds remarkably inhibited chondrogenesis of MSCs. These ECM scaffolds not only can provide new 3D ECM models to investigate the effects of ECM on MSCs functions, but also can be used as favorable ECM scaffolds for tissue engineering.